Synthesis and Evaluation of Chalcone Derivatives as Inhibitors of Neutrophils' Chemotaxis, Phagocytosis and Production of Reactive Oxygen Species. (28th October 2013) - Bukhari, Syed N. A.; Tajuddin, Yasmin; Benedict, Vannessa J.; Lam, Kok W.; Jantan, Ibrahim; Jalil, Juriyati; Jasamai, Malina
<x xml:space="preserve">Abstract</x> Inhibitory effects on neutrophils' chemotaxis, phagocytosis and production of reactive oxygen species (ROS) are among the important targets in developing anti‐inflammatory agents and immunosuppressants. Eight series of chalcone derivatives including five newly synthesized series were assessed for their inhibitory effects on chemotaxis, phagocytosis and ROS production in human polymorphonuclear neutrophils (PMNs). Inhibition of PMNs' chemotaxis and phagocytosis abilities were investigated using the Boyden chamber technique and the Phagotest kit, respectively, while ROS production was evaluated using luminol‐ and lucigenin‐based chemiluminescence assay. The new derivatives (4d and 8d), which contain 4‐methylaminoethanol functional group were active in all the assays performed. It was also observed that some of the compounds were active in inhibiting chemotaxis while others suppressed phagocytosis and ROS production. The information obtained gave new insight into chalcone derivatives with the potential to be developed as immunomodulators.